Indigenous community-based education - May, Stephen, 1962- (Multilingual Matters, 1999)
"This edited collection aims to highlight, promote and extend the understanding of indigenous community-based education. Based on the wider principle of self-determination, indigenous community-based education programmes involve indigenous communities taking control of their education in order to retain and promote their indigenous languages and cultures more effectively, and improve the educational achievement of indigenous students."--Jacket